2018
DOI: 10.1021/acs.jafc.8b05794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variations in the Fatty Acid Residue of Lactose Monoesters on Their Emulsifying Properties and Biological Activities

Abstract: Lactose fatty acid esters are high-value-added derivatives of lactose and represent a class of biodegradable, nonionic, low-molecular-weight surfactants (emulsifiers) that have considerable potential in the food, cosmetic, and pharmaceutical industries. Certain lactose esters have also garnered attention for their biological activities. In this work, we detail syntheses of a homologous series of 6′-O-acyllactose esters of varying alkyl chain length (from 6 to 18 carbons) and report on their activities as surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 49 publications
6
35
0
Order By: Relevance
“…We have found that such raffinose esters embodying appropriately hydrophobic acyl side-chains display distinctive and excellent surfactant effects, especially in oil-in-water emulsions. Previously, we have shown that certain disaccharide (lactose, maltose)-derived esters exhibit emulsifying properties superior to those of their commerciallydeployed and sucrose-based counterparts [4,8]. Similar to such earlier observations [4,8,25], we have now found that the performance of raffinose monoesters as surfactants is largely determined by the length of the associated acyl chain.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We have found that such raffinose esters embodying appropriately hydrophobic acyl side-chains display distinctive and excellent surfactant effects, especially in oil-in-water emulsions. Previously, we have shown that certain disaccharide (lactose, maltose)-derived esters exhibit emulsifying properties superior to those of their commerciallydeployed and sucrose-based counterparts [4,8]. Similar to such earlier observations [4,8,25], we have now found that the performance of raffinose monoesters as surfactants is largely determined by the length of the associated acyl chain.…”
Section: Discussionsupporting
confidence: 81%
“…It is one of the standard means for classifying surfactants, with a high HLB value being above 11 and a low one being below 9 [26]. Usually, HLBs are predicted by assigning values, as described by Griffin [27], to the given structure or by experimental measurement using, for example, the water number method [8]. Since raffinose is a trisaccharide containing a sucrose substructure, the higher hydrophilicity of raffinose (relative to sucrose) would be expected to result in higher HLB values for the corresponding esters.…”
Section: Surface-active Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although some of the sugar-based esters here presented have already been published for other applications and also as possible antibacterial agents [22][23][24][29][30][31][32][33], a detailed comparative study concerning the properties of a relative large number of both aliphatic and aromatic amphiphilic carbohydrate esters as antimicrobial (Gram-positive, Gram-negative, and fungi) and mostly antibiofilm agents is still lacking.…”
Section: Scheme 3 Reagents and Conditions: (mentioning
confidence: 99%
“…In these few cases, chemical esterification could be the main road to explore. Among all sugar-based surfactants, sucrose and glucose esters are the most studied and applied derivatives [21][22][23][24], while other derivatives, such as lactose esters, which can be easily obtained from waste whey, and mannose esters, have received less attention.…”
Section: Introductionmentioning
confidence: 99%